2008
DOI: 10.1242/jeb.013169
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of metabolism inHelix aspersasnails: changes through ontogeny and response to selection for increased size

Abstract: SUMMARYThough many are convinced otherwise, variability of the size-scaling of metabolism is widespread in nature, and the factors driving that remain unknown. Here we test a hypothesis that the increased expenditure associated with faster growth increases metabolic scaling. We compare metabolic scaling in the fast-and slow-growth phases of ontogeny of Helix aspersa snails artificially selected or not selected for increased adult size. The selected line evolved larger egg and adult sizes and a faster sizespeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 56 publications
6
75
0
Order By: Relevance
“…Several studies in diverse species of plants [193], invertebrates [103,105,136,219,220,222] and vertebrates [218,221,223,224] have shown that increased growth rate is associated with steeper ontogenetic scaling of metabolic rate (slopes often approaching 1) (also see 19,20,98]. This support involves not only numerous correlative analyses, but also multiple experimental manipulations.…”
Section: Resource-demand Modelsmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies in diverse species of plants [193], invertebrates [103,105,136,219,220,222] and vertebrates [218,221,223,224] have shown that increased growth rate is associated with steeper ontogenetic scaling of metabolic rate (slopes often approaching 1) (also see 19,20,98]. This support involves not only numerous correlative analyses, but also multiple experimental manipulations.…”
Section: Resource-demand Modelsmentioning
confidence: 98%
“…For example, Teissier (1931) showed that nutrition-enhanced growth rate resulted in steeper scaling of metabolic rate in mealworm larvae (Tenebrio molitor) [222]. A similar outcome occurred in brown garden snails (Cornu asperum, formerly Helix aspersa), whose growth rate had been increased by artificial selection for increased body size [220]. A natural experiment involving varying natural selection on growth rate in amphipod populations living in springs with versus without visually hunting fish predators also revealed a close match between the ontogenetic scaling of the rates of growth and metabolism [105,136].…”
Section: Resource-demand Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…An exponent of 1 represents isometric scaling, where metabolic rate increases in direct proportion to body mass, while an exponent different from 1 indicates that metabolic rate scales allometrically and does not increase in direct proportion to body mass (Kleiber 1947;Hayssen and Lacy 1985). Generally, interspecific scaling exponents fall between 2/3 and 1 (Niven and Scharlemann 2005;Chown et al 2007;White et al 2007), but intraspecific relationships show a much wider range of values (Bokma 2004;Glazier 2005;Chown et al 2007;Killen et al 2007Killen et al , 2010Moran and Wells 2007;Czarnoleski et al 2008;Moses et al 2008;White et al 2011). While body mass does account for much of the variation in metabolic rate, there persists a common finding of considerable residual variation in both interspecific and intraspecific scaling of metabolic rate, such that the metabolic rates of similarly sized animals can differ by several fold (Glazier 2005(Glazier , 2010.…”
Section: Effect Of Thermal Acclimation On Organ Mass Tissue Respiratmentioning
confidence: 99%
“…Here, we test the metabolic consequences of variation in early life thermal environment, using a 2 # 2 experimental design of captive-born neonatal garter snakes of both ecotypes reared under thermal conditions designed to mimic field ecological differences. We report measures of the resting metabolic rate of individual snakes at four temperatures spanning the natural activity range of this species, first-year growth, and growth efficiency (defined as increase in size per unit of food consumed ;Ivlev 1945;Czarnołęski et al 2008). Because temperature affects metabolic rate and, concomitantly, energy intake and growth, we are able to test for plasticity and subsequent developmental canalization of metabolic pathways resulting from early life-history experiences.…”
Section: Introductionmentioning
confidence: 99%